Privacy-Preservation Techniques for IoT Devices: A Systematic Mapping Study - Damiano Torre; Anitha Chennamaneni; Alex Rodriguez (IEEE Access, 2023)
The Internet of Things (IoT) is becoming a pervasive technology entangled in everyday life. The objective of IoT is to provide ubiquitous access to numerous devices and machines on service providers. However, IoT-based devices may expose a user to various privacy and security threats. Privacy-preservation techniques focus on securing any type of data transfer between different parties. We aim to deliver the current state of the art in terms of privacy-preservation techniques used for IoT devices that have been discussed in the literature. Therefore, we carried out a systematic identification of the privacy-preservation techniques for IoT devices that have been described in the cybersecurity domain. To do so, we followed rigorous guidelines to define our research protocol to increase the repeatability and reliability of our results. A set of ten research questions was created to drive the analysis of our study. This research work comprehensively analyzes and discusses the privacy-preservation techniques for IoT devices published in five different academic venues. We identified 260 studies, mostly published between 2017 and 2021, that were systematically selected from an initial set of 1394 papers. The most active research areas in privacy-preservation techniques for IoT devices discuss cryptography techniques to improve the authentication process to access IoT devices. The majority of authors presented privacy-preservation techniques for IoT that involved inventory privacy threats and discussed privacy interference attacks. We comprehensively analyze and discuss the trends, gaps, and possible future research directions of the privacy-preservation techniques used for IoT devices published in different academic venues.